Impact evaluation of community management of rice-fish system in Assam - Baruah, Uttam Kumar; Talukdar, Rajendra K; Goswami, Umesh C; Bhagowati, Ajit Kumar (Indian Journal of Fisheries, 2011)
The present study deals with the community management of rice-fish system in an area of 66.8 ha at a remote village of Jhuria, Nagaon, Assam. The study reveals the farmers’ positive attitude towards the efficacy of collective action in management of rice - flood, and a change in the concept of access to resource by right. The farmers realised the benefits of managing the rice-fish system collectively rather than individually. They obtained a yield of 2,100-2,300 kg of rice grain per ha and 400-450 kg fish per ha and around 30,000 carried over fish seed. The fish yield was equivalent to 2,209 kg rice grain per ha. The experience resulted in more favourable attitude towards common management of rice-flood, increased satisfaction with fish yield and the development of a strong sense of belonging to the group. More ponds were either dug or enlarged